CURRENT STATUS OF DRUG-RESISTANCE OF M.TUBERCULOSIS AND POSIBILITY OF ITS GENOTYPING DETECTION - Antonenko, P.B.; Kresyun, V.I.; Filuk, V.V.; Antonenko, K.O.; Stokich, V.G.; Korotich, N.Ya. (World of Medicine and Biology, 2014)
Recently a method of polymerase-chain reaction (PCR) is getting more value than before for detection of drug-resistance of Mycobacterium tuberculosis strains (MBT). Thus the goal of the present study was to evaluate the spreading of MBT drug-resistance and dynamics of spreading of the mutations, which lead to drug-resistance, in MBT genotype with the help of PCR. It was done an analysis of drug-susceptible tests for Ist line antituberculosis drugs in bacteriological department of Odessa district antituberculosis dispensary in 2012. By the PCR it was done the detection of mutations in katG, inhA genes, which are responsible for isoniazid-resistance, and in rpoB gene that are associated with rifampicin-resistance. The obtained data has been compared with results of 2006 research.According to received data during 2000-2006yy. in Odesa region there was a significant raising of the drug-resistance to the Ist-line antituberculosis agents in MBT. In 2012 y. 54,8% of isolates cultures belonged to Beijing family, which is characterized by severe course of tuberculosis (TB), in 2006 and 2003 this index was 43,0% and 39,6% correspondently. During detection of isoniazid-resistance of MBT by PCR-method it was found that the finding of mutation in katG and/or inhA gene had the highest sensitivity (100%), while finding of mutation in katG gene had the primary selectivity (80,1%). The sensitivity of rifampicin-resistance investigation by detection of mutations in rpoB gene was 87,0%, the sensitivity – 90,2%. In 2006 y. among DNA-isolates of MBT cultures the level of the mutations in rpoB and katG genes was 44,9% and 54,2% correspondently, in the same time in 2012 y. – it was 22,1% and 34,6% correspondently.
Keywords: katG gene; inhA gene; rpoB gene; drug-resistance; tuberculosis